UJI KETERBACAAN TEKS PARABEL SISWA SD KELAS IV SEMESTER 1 - Chelsea Raihan Sefilla; Fadilatul Almashita; Yusuf, Fauzi; Neza; Olina Yufika; Chandra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the readability level of children's story texts in the textbook "Saya Senang Berbahasa Indonesia untuk Sekolah Dasar Kelas IV Semester 1" using the Fry Graph. This research applies a quantitative approach with descriptive methods. The objects of this study were five children's story texts selected from the textbook. Data collection was carried out through documentation studies by taking samples of 100 words from each text to calculate the number of sentences and syllables. The results showed variations in readability levels across the analyzed texts: two texts (40%) matched the 4th-grade level ("Lebih Beruntung" and "Buku-Buku Dimas"), one text (20%) was suitable for 3rd-to-4th-grade level ("Si Elok yang Hampir Punah"), one text (20%) was at the 5th-grade level ("Seni Tari"), and one text (20%) was at the 8th-grade level ("Matilda Si Jenius"). These findings indicate that not all story texts in the textbook match the reading ability of fourth-grade elementary school students. Therefore, teachers need to evaluate and select teaching materials carefully to align with students' reading levels.